Early Tocilizumab Dosing Is Associated With Improved Survival in Critically Ill Patients Infected With Severe Acute Respiratory Syndrome Coronavirus-2. (29th March 2021) - Petrak, Russell M.; Van Hise, Nicholas W.; Skorodin, Nathan C.; Fliegelman, Robert M.; Chundi, Vishnu; Didwania, Vishal; Han, Alice; Harting, Brian P.; Hines, David W.
Abstract : Objectives: To identify the most efficacious timing for tocilizumab administration in critically ill patients infected with severe acute respiratory syndrome coronavirus-2. Design: Observational multicenter cohort study. Setting: A total of 23 acute care hospitals in four states. Patients: One-hundred eighteen patients admitted between March 13, 2020, and April 16, 2020. Eighty-one patients received tocilizumab, and 37 were untreated and served as a control group. Measurements and Main Results: The main outcome was mortality and was analyzed by timing of tocilizumab dosing. Early dosing was defined as a tocilizumab dose administered prior to or within 1 day of intubation. Late dosing was defined as a dose administered greater than 1 day after intubation. A control group that was treated only with standard of care, and without tocilizumab, was used for comparison. Early tocilizumab therapy was associated with a statistically significant decrease in mortality as compared to patients who were untreated ( p = 0.003). Dosing tocilizumab late was associated with an increased mortality compared with the untreated group ( p = 0.006). Conclusions: Early tocilizumab administration was associated with decreased mortality in critically ill severe acute respiratory syndrome coronavirus-2 patients, but a potential detriment was suggested by dosing later in a patient's course.